PERAMALAN PENJUALAN JASA FREIGHT FORWARDING DENGAN METODE SINGLE MOVING AVERAGES, EXPONENTIAL SMOOTHING DAN WEIGHTED MOVING AVERAGES (Studi kasus pada PT Anugerah Tangkas Transportindo, Jakarta) - Reza Dimas Syahputra; Suharyono Suharyono; Supriono Supriono (Jurnal Administrasi Bisnis, 2018)
This research is intended to find out more about how to forecast and to find out how many is the total sales of freight forwarding service in PT. Anugerah Tangkas Transportindo. To determine sales forecasting freight forwarding service on the PT. Anugerah Tangkas Transportindo using the Single Moving Averages 3 montht and 4 month period, Exponential Smoothing (α = 0.1; α = 0.5; α = 0.9), Weighted Moving Averages 3 period . For the measurement error (error) using the Mean Absolute Deviation (MAD) and Mean Square Error (MSE). Based on this research can be concluded that, the most appropriate method is applied to the PT. Anugerah Tangkas Transportindo is a Exponential Smoothing α = 0.1 if they are compared to Single Moving Averages 3 month and 4 month period, Exponential Smoothing (α = 0.5; α = 0.9), Weighted Moving Averages 3 period. The result of sales forecasting method Exponential Smoothing α = 0.1 is 1215 sales of forecasting freight forwarding services, amounting to 81,59  MAD (Mean Absolute Deviation) and 11090,1 MSE (Mean Square Error). Keywords : Freight Forwarding, Single Moving Averages, Exponential Smoothing, Weighted Moving Averages, Mean Absolute Deviation (MAD), Mean Square Error (MSE). ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana cara meramalkan dan mengetahui berapa jumlah penjualan jasa freight forwarding pada PT. Anugerah Tangkas Transportindo. Untuk mengetahui peramalan penjualan jasa freight forwarding dengan menggunakan metode Single Moving Averages periode 3 bulanan dan 4 bulanan, Exponential Smoothing (α = 0.1; α = 0.5; α = 0.9), Weighted Moving Averages dengan 3 bulanan pada bulan September 2017. Untuk pengukuran kesalahan (error) menggunakan Mean Absolute Deviation (MAD) dan Mean Square Error (MSE). Berdasarkan hasil penelitian menunjukkan bahwa,metode  analisis Exponential Smoothing α = 0.1 merupakan metode yang unggul dari segi keakuratan nya dalam meramalkan dibandingkan dengan metode Single Moving Averages periode 3 bulanan dan 4 bulanan, Exponential Smoothing (α = 0.5; α = 0.9), Weighted Moving Averages dengan bobot 3. Hasil peramalan penjualan dengan metode Exponential Smoothing α = 0.1 adalah 1215 permintaan atau penjualan jasa freight forwarding. Adapun tingkat kesalahan peramalan, MAD (Mean Absolute Deviation) sebesar 81,59 dan MSE (Mean Square Error) sebesar 11090,1. Kata Kunci : Freight Forwarding, Single Moving Averages, Exponential Smoothing, Weighted Moving Averages, Mean Absolute Deviation (MAD), Mean Square Error (MSE).